Stoking the Fire: What Makes a Teacher Inspirational? - Powell-Brown, Ann; Buchanan-Butterfield, Dawna Lisa; Yao, Yuankun (Educational (Re)naissance, 2014)
Abstract This essay uses qualitative elements to examine characteristics of inspirational teachers through the eyes of teacher candidate autobiographical essays. Based on narratives written by 35 college students, three teacher educators examined the responses through several lenses, including: the characteristics the inspirational teachers had in common, and the impact the teachers had on the students. Seven emerging themes indicate that truly inspirational teachers go beyond the normal call of their duties, sometimes in intangible ways. Also indicated is the notion that knowledge and instructional strategies are not sufficient for making a teacher inspirational. Implications for teacher education are discussed.